Dukungan Interpersonal untuk Kebutuhan Psikologis Dasar dan Hubungannya Dengan Motivasi, Kesejahteraan, dan Kinerja: Analisis Meta - Hamzan Wadi; Emha Zainul Mukminin (Alpatih Harapan Semesta, 2024)
Interpersonal support plays an important role in meeting an individual's basic psychological needs, which include the need for autonomy, competence, and social relationships. This study aims to examine the relationship between interpersonal support for basic psychological needs and motivation, well-being, and performance through meta-analysis. Based on relevant research, this analysis identifies the influence of interpersonal support on each of these aspects, as well as how these relationships interact with each other. The results of the analysis show that adequate interpersonal support contributes significantly to increasing intrinsic motivation, improving psychological well-being, and encouraging increased individual performance in various contexts, both at work and in personal life. Social support that strengthens an individual's basic psychological needs, such as respect for autonomy, empowering competence, and maintaining positive relationships, has been proven to act as an important supporting factor for achieving optimal results in various fields. These findings provide new insights into how supportive social environments can strengthen a healthy psychological foundation, as well as provide recommendations for intervention practices aimed at improving individual well-being and performance, both in professional and personal contexts. Overall, this research highlights the important role of interpersonal support in supporting basic psychological needs and strengthening individual motivation, well-being and performance, as well as providing a basis for the development of policies and programs that are more effective in improving individuals' quality of life holistically.